Application of Simplex Lattice Design in Formulation and Development of Buoyant Matrices of Dipyridamole - Mandlik Satish K, Adhikari Saugat, Deshpande Ameya A. (Journal of Applied Pharmaceutical Science)
The present study describes the design and development of buoyant matrices of dipyridamole. The matrices were prepared by direct compression method using simplex lattice design as an optimization technique. Amount of HPMC K4M (X1), sodium bicarbonate (X2) and ethyl cellulose (X3) were used as the independent variables where floating lag time (Y1) and percentage drug release at 6h (Y2) were considered as the response variables. As per the simplex lattice design total 7 formulations were formulated. Matrices were evaluated for physical parameters, in-vitro buoyancy, in-vitro drug release, water uptake studies. Drug release data was fitted into different kinetic models. The results of response variables were statistically evaluated using design expert 8.0 software. Polynomial models were generated for all the response variables using multiple linear regression analysis (MLRA) approach. A statistical model incorporating 7 interactive terms was used to evaluate the responses. The results of response variables are expressed for model analysis by Scheffe’s special cubic model. Graphical representation was done by response surface plots and contour plots. The resulted model equation showed that factor X1 responsible for prolongation of drug release. On the basis of acceptance criteria the formulation coded by DP3 was selected as a promising formulation from the simplex lattice batches which fitted best to zero order release kinetic model.
Keywords: Dipyridamole, Mixture Design, Simplex lattice design, Buoyant matrices, Controlled release, HPMC